COMPARATIVE EFFECT OF LECTURE METHOD AND MULTIPLE INSTRUCTIONAL APPROACH ON STUDENTS’ COGNITIVE ACHIEVEMENT IN BASIC TECHNOLOGY IN OSUN STATE (NAU Journal of Technology and Vocational Education, 2024)
The study compared the effect of lecture method and multiple instructional approach onstudents’ cognitive achievement in basic technology. Two research questions were answered andtwo null hypotheses were tested at 0.05 level of significance. Quasi-experimental design wasadopted for the study, specifically, the non-equivalent control group design. The study wascarried out in Ilesa Education Zone of Osun State. The population of the study was 1,876 JSStwo students, while the sample comprised 80 JSS two students drawn from two intact classes intwo junior secondary schools in Ilesa. Experimental group was taught using multipleinstructional approach, while the Control group was taught using lecture method. The treatmentlasted for four weeks after pretest has been administered using Basic Technology AchievementTest (BTAT) as instrument for data collection. The instrument was subjected to face and contentvalidity. Test-retest method was adopted to establish reliability of the instrument which yielded acoefficient of 0.75. Data collected were analyzed with mean and analysis of covariance(ANCOVA). The result revealed that students taught with multiple instructional approachperformed better than students taught with lecture method in basic technology. There was nosignificant difference in the mean scores of male and female students in basic technology afterthe treatment. Based on the findings of the study, it was recommended that relevant agenciesshould instruct basic technology teachers to adopt multiple instructional approach when teachingto enhance students’ cognitive achievement.
Keywords: Basic technology, cognitive achievement, lecture method, multiple instructional approach.